2021
DOI: 10.1093/rap/rkab027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychosocioeconomic impact of COVID-19 pandemic on patients of the Indian Progressive Systemic Sclerosis Registry (IPSSR)

Abstract: Objectives The aim was to determine the impact of the coronavirus disease 2019 (COVID-19) pandemic on access to health care among patients with scleroderma and to analyse the economic and psychosocial impacts and the infection prevention measures taken by them during the pandemic. Methods A 25-item questionnaire designed to assess the components of the objectives was tele-administered between October 2020 and January 2021 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One of the main challenges faced by individuals with RMDs during the pandemic was the inability to access routine health care [ 24 , 25 ] and the lack of information about continuing immunosuppressive agents [ 26 ]. This resulted in drug discontinuation in a substantial proportion of patients [ [27] , [28] , [29] ], which predisposes to a flare of the underlying RMD. A second hit in the form of COVID-19 infection may potentially portend poorer prognosis in those with uncontrolled RMD and may have resulted in higher hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main challenges faced by individuals with RMDs during the pandemic was the inability to access routine health care [ 24 , 25 ] and the lack of information about continuing immunosuppressive agents [ 26 ]. This resulted in drug discontinuation in a substantial proportion of patients [ [27] , [28] , [29] ], which predisposes to a flare of the underlying RMD. A second hit in the form of COVID-19 infection may potentially portend poorer prognosis in those with uncontrolled RMD and may have resulted in higher hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…The assessors are rheumatology trainees with more than 1 year of experience in routinely performing NFC examination in clinics and are a part of the Indian Progressive Systemic Sclerosis Registry (IPSSR). 18 For this study, they additionally underwent training with 20 dummy cases each before being assigned the task of reporting findings.…”
Section: Methodsmentioning
confidence: 99%
“…11 Similar results emerged from Indian Progressive Systemic Sclerosis Registry, where the pandemic fear was a cause of missed outpatients visits and job loss was found associated to a self-reported worsening of disease. 14 Another work from the SPIN COVID-19 cohort showed that variables associated with COVID-19 fear were interference of breathing problems in daily activities, financial resources inadequacy, and high levels of previous anxiety. 13 Our study identifies for the first-time higher amounts of COVID-19-related fear and generalized anxiety disorder symptoms in the subgroup of SSc patients who missed regular visits, evidenced by validated questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…13 Pandemic fear was described by patients as a major cause of missed outpatient visits, as emerged from a tele-survey of Indian Progressive Systemic Sclerosis Registry. 14 For SSc patients, assiduous follow-up is essential to prevent or limit disease multi-organ involvement through appropriate diagnostic and therapeutic tools to achieve a better disease outcome. 15 Anxiety and fear due to COVID-19 thus emerged as marking psychological fragility in SSc patients in the course of the current pandemic.…”
Section: Introductionmentioning
confidence: 99%